Central African Republic : Request for a Three-Year Arrangement under the Extended Credit Facility-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for the Central African Republic. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Central African Republic's (CAR) Request for a Three-Year Arrangement Under the Extended Credit Facility. Consistent with the IMF's Country Engagement Strategy, the IMF-supported program is expected to support the implementation of the peace agreement and of CAR's medium-term development strategy. Its main objectives are to maintain macroeconomic stability, strengthen administrative capacity, governance, and the business climate, and address CAR's protracted balance of payments needs. Fiscal policy will focus on revenue mobilization, spending prioritization, and strengthening public financial management, with a view to allow, over the medium term, the durable financing of CAR's considerable security, social, and infrastructure spending needs. Structural reforms will aim at improving the government's capacity to design and implementing policies and reforms, at enhancing governance, including through strengthening anticorruption institutions, and at removing bottlenecks and regulatory impediments to private investment. The new arrangement will also help catalysing external concessional financing from other development partners, which is critical to support CAR's path out of fragility. The IMF will also continue its extensive capacity development on priorities that are aligned with the program objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet